The anatomy of concussion and chronic traumatic encephalopathy: A comprehensive review. Issue 3 (21st December 2018) - Singla, Amit; Leineweber, Bridget; Monteith, Stephen; Oskouian, Rod J.; Tubbs, R. Shane
Abstract : Concussion is defined as a complex pathophysiological process that affects the brain as a result of traumatic biomechanical forces. Repeated unrecovered concussions can result in chronic brain injury syndrome which is referred to in the literature today as chronic traumatic encephalopathy." There is an exponential increase in public and political interest in this condition in the recent times resulting in a significant investment in research to improve the current understanding of the disease, ways to decrease its incidence and determine its prognosis. Broadly the research involves three main disciplines of medicine including neuropathology, neuroradiology and biological markers. Although progress has been made, to date there is no definite pathological, radiological or neurobiological marker which has shown consistent promise to make the diagnosis and prognosticate the disease. Possible reasons are multiple such as inconsistencies in the methods studies have used, different time periods in which the tests were conducted, the small numbers of subjects included in the studies, and inconsistencies in the definitions of concussion or mild traumatic brain injury. Herein, we present a comprehensive review of the current literature on this topic. Positron emission tomography scans with radioactive ligands such as T807 as an imaging biomarker, and neurofilament light and ubiquitin C‐terminal hydrolase as serum biomarkers have shown some promise lately in diagnosing concussion and chronic traumatic encephalopathy and also determining their prognosis. Clin. Anat. 32:310–318, 2019. © 2018 Wiley Periodicals, Inc.